In situ and in vitro ruminal starch degradation of grains from different rye, triticale and barley genotypes. (21st February 2017) - Krieg, J.; Seifried, N.; Steingass, H.; Rodehutscord, M.
Abstract : In recent years, advances in plant breeding were achieved, which potentially led to modified nutritional values of cereal grains. The present study was conducted in order to obtain a broad overview of ruminal digestion kinetics of rye, triticale and barley grains, and to highlight differences between the grain species. In total, 20 genotypes of each grain species were investigated using in situ and in vitro methods. Samples were ground (2 mm), weighed into polyester bags, and incubated in situ 1 to 48 h in three ruminally cannulated lactating dairy cows. The in vitro gas production of ground samples (1 mm) was measured according to the 'Hohenheim Gas Test', and cumulative gas production was recorded over different time spans for up to 72 h. There were significant differences ( P <0.05) between the species for most parameters used to describe the in situ degradation of starch (ST) and dry matter (DM). The in situ degradation rate ( c ) and effec tive degradability (assuming a passage rate of 8%/h; ED8) of ST differed significantly between all grains and was highest for rye (rye: 116.5%/h and 96.2%; triticale: 85.1%/h and 95.0%; barley: 36.2%/h and 90.0% for c and ED8, respectively). With respect to DM degradation, the ranking of the species was similar, and predicted c values exhibited the highest variation within species. The in vitro gas production rate was significantly higher ( P <0.05) for rye than for triticale and barley (rye: 12.5%/h; triticale: 11.5%/h; barley: 11.1%/h). A positive relationship between the potential gas production in vitro and the maximal degradable DM fraction in situ was found using all samples ( r =0.84; P <0.001) as well as rye ( P =0.002) and barley ( P <0.001) alone, but not for triticale. Variation in ruminal in situ degradation parameters within the grain species resulted from the high c values, but was not reflected in the ED estimates. Therefore, the usage of mean values for the ED of DM and ST for each species appears reasonable. Estimated metabolisable energy concentrations (ME, MJ/kg DM) and the estimated digestibility of organic matter (dOM, %) were significantly lower ( P <0.05) for barley than for rye and triticale. Rye and triticale dOM and ME values were not significantly different ( P =0.386 and 0.485).